Do’a Sang Pemimpi(N) : Belajar dari Proklamator - Arfin, Antoni Ludfi; Winardono, Agus (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2024)
Research aim: This research examines the characteristics of a visionary Leader. Methods: This research is qualitative through a literature review related to leaders' vision, opportunities, and uniqueness (amaze yourself). Research Finding: Visionary leaders have a long-term vision for the organization's future, set clear goals, inspire subordinates, and allocate resources effectively to achieve organizational objectives. The three characteristics that visionary leaders should possess, as summarized by the acronym DOA—Developing a vision, seeking opportunities, and amazing yourself—are essential for achieving these goals. Theoretical contribution/Originality: The results of this research contribute theoretically by providing both theoretical and empirical evidence on the characteristics of dreamers, specifically: Develop Vision, Opportunities Seeker, and Amaze Yourself Practitioner/Policy implication: This research offers valuable contributions for leaders in education, profit-organization, and non-profit organizations to develop a forward-looking vision, seek opportunities, and leverage their unique potential/to amaze themselves. Research limitation: Further research is needed on these three characteristics, especially in the field of corporate businesses